Phenomenological study of thermal aging effects on intermetallic growth mechanisms and shear strength behavior of wafer level solder bumps - Amistoso, Jose Omar S. (2007., 2007)
The effect of wafer level solder bump size on solder bump strength and intermetallic growth as a function of time, at different storage temperatures is studies, using solder bumps of two different heights :95 um (SB95) and 142 um (SB142). Smaller solder bumps (SB95) lead to a faster decrease in bump shear strength. Increasing aging temperature and time brings about an increase in the final fracture area of the solder, and It is observed that the smaller solder bump (SB95) exhibits a faster rate of increase in final fracture area, than the bigger bump. A linear decrease of solder bump strength with intermetallic thickness is established for the systems studied.
Increasing Au thickness of the UBM from 80 to 120 nm does not have a significant effect on the bump shear strength of the solder bumps studied. Differences observed in the bump shear strength degradation between SB95 and SB142 may be attributed to a concentration gradient effect wherein a higher Ni-to-solder concentration gradient of Ni atoms is observed in a region close to the Ni-intermetallic interface, with the smaller solder bumps. There is also a higher concentration gradient of both Cu and Sn atoms from the solder to a region close to the Ni-intermetallic interface. The general decrease in bump shear strength for both wafer types studied can be attributed to the increase in voids that occur within the solder near the solder bump to UBM interface that may be attributed to the growth of (Cu, Ni)6Sn5 intermetallic in the solder. Furthermore, it is established that the final fracture area increases linearly with an increase in intermetallic thickness and a decrease in solder bump shear strength.
The overall intermetallic growth activation energies for the two solder bump sizes are found to be comparable, at 0.85 eV for the wafer with smaller solder bumps and 0.86 eV for the one with larger solder bumps. For this study, (Cu, Ni)6Sn5, is initially formed, at the solder bump to UBM interface, followed by the formation of (Ni,Cu)3Sn4, facing the Ni layer. Other intermetallics identified are Ag3Sn which extends as an outgrowth from the solder bump-to-UBM interface and AuSn4, which occurs within the solder bump matrix.
Thesis (Ph.D. Materials Science Engineering)--University of the Philippines, Diliman.
Keywords: Integrated circuits -- Wafer-scale integration; Solder and soldering; Shear (Mechanics)